Patchouli Oil Production for Fixative Aromatheraphy: A Case Study Design of Condenser for Steam Distillation - Egi Agustian; Anny Sulaswatty (Balai Riset dan Standardisasi Industri Pontianak, 2015)
Patchouli oil is an important material for aromatherapy industries and made from patchouli leaves by steam distillation. The important parts of steam distillation is condenser. The problem is process of farmer's patchouli based on experience not used chemical process of steam distillation cause not effective and efficient. The study was designed of condensers on steam distillation for patchouli leaves. Specification of condenser type is shell and tube, stainless steel material and water as coolant. Tubing sized is ¼ inch with 500 mm of length and 24 pieces. Shell measuring 2.5 inch and 600 mm of length. The performance of condenser gave the efficiency at 94.51%. The process condition of ratio stems to leaves is 5:6 and 4.5 hours was considered ideal for steam distillation. The used of energy is lowest cause the efficiency condenser and yield will be higher. Patchouli oil yield of 2.39% and patchouli alcohol content is 35.65%.